Press Conference and Vigil re Protesting Jerry Falwell Speaking at Piccadilly Inn Airport - Watkins, Howard::::::::: (1984)
Protesters on McKinley Avenue with banner "FRESNANS FOR: DIVERSITY, CIVIL LIBERTIES, FREEDOM OF THOUGHT, AND SEPARATION OF CHURCH AND STATE